DNA TOUCH STR CODIS AS LEGITIMATE EVIDENCE IN UNCOVERING CRIMINAL ACTS - Nurdianto, Arif Rahman; Setiawan, Fery; Yudianto, Ahmad; Nurdianto, Rizal Fauzi; Sunariani, Jenny (Universitas Airlangga, 2024)
The identification process at the crime scene (TKP) is one of the essential tasks carried out by police investigators. One critical aspect is the collection and analysis of evidence found at the crime scene, referred to as biological evidence (BB). This evidence serves as a crucial source for determining whether an incident occurred and, if so, whether it was a suicide or another criminal act (such as murder, etc.). The biological evidence found can be analyzed using molecular serobiology approaches, which are rapidly advancing in the fields of forensic medicine and medicolegal practice. One such approach involves utilizing DNA traces, although a common challenge is that often the DNA recovered at crime scenes is degraded. Therefore, a DNA amplification method utilizing the Polymerase Chain Reaction (PCR) technique, along with the short tandem repeat (STR) – CODIS identification approach, is necessary. The analysis of DNA traces using the STR-CODIS approach enables investigators to determine whether the incident was purely criminal, a suicide, or another type of accident involving the victim. Furthermore, the DNA analysis using the STR-CODIS method can also aid in identifying the victims discovered at the crime scene.